Effect of season, soil type and fertilizer on the biomass production and chemical composition of five tropical shrub legumes with forage potential - Tiemann, Tassilo T.; Franco, LH; Peters, Michael; Frossard, Emmanuel; Kreuzer, M.; Lascano Aguilar, Carlos Eduardo; Hess, H.D. (Wiley, 2009)
The biomass production and the nutritive value of three tropical shrub legumes with condensed tannins (CT) (Calliandra calothyrsus, Flemingia macrophylla, Leucaena leucocephala) and two without CT (Cratylia argentea, Desmodium velutinum) as nitrogen‐rich feed supplements for ruminants were assessed in two field experiments in Colombia. In one experiment, conducted on two different typical tropical soils (mollisol vs. oxisol; pH, 7·8 vs. 5·0; P content, 43 vs. 2 mg kg DM−1), the effects of low and high levels of fertilizer application with P, K, Ca, Mg and S were tested in both the dry and rainy seasons. In a second experiment on the oxisol, the effect of a lower level of application of either P or S fertilizer was assessed. On the oxisol, C. calothyrsus and F. macrophylla had the highest biomass production (93 and 100 g DM plant−1 in 9 weeks respectively) but the dry season caused extremely low DM yields in all species tested. Leucaena leucocephala did not grow on the oxisol but had the highest biomass production on the mollisol (454 g DM plant−1 in 9 weeks). On the oxisol, the mineral concentrations of the forage were below the requirements of ruminant livestock. Fertilizer treatment had no clear effects on the nutrient composition of the forage. The non‐CT shrub C. argentea had the highest concentrations of most minerals in its forage.